Comparison of Roundtable On Sustainable Palm Oil (RSPO), Indonesian Sustainable Palm Oil (ISPO), and Malaysian Sustainable Palm Oil (MSPO) - Wulandari, Ayu; Nasution, Muhammad Ansori (Jurnal Penelitian Kelapa Sawit, 2021)
The palm oil industry is an industry that has a role in a country’s economic sector. The palm oil industry needs certification standards in strengthening industrial systems and steps to remain sustainable. Industrial systems that are strengthened based on economic, legal, social, and environmentally friendly. Implementing sustainable palm oil certification standards include the Roundtable on Sustainable Palm Oil (RSPO), Indonesian Sustainable Palm Oil (ISPO), and Malaysian Sustainable Palm Oil (MSPO). This study aims to compare the three certification standards and find out the most comprehensive certification standards. This research method uses qualitative methods that are descriptive and comprehensively analyzed from each indicator. The results of this study indicate that the total RSPO, ISPO and MSPO assessments amounted to 77 points, 56 points, and 62 points respectively, so it can be concluded that the RSPO has a more comprehensive level of detail and requirements compared to ISPO and MSPO based on aspects of the certification system, supply chain system, social and environmental protection, treatment of smallholders/plasma, peatlands and land acquisition.